PENGARUH TEKNOLOGI KOMUNIKASI INFORMASI PADA IMPLEMENTASI KONSEP GEO-OFFICE - Sari, Sriti Mayang (Institute of Research and Community Outreach - Petra Christian University, 2006)
The improvement of the development of information communication technology seen through the presence of various technological features provides people with various eases of communication and choices to work anywhere and anytime. The development of information communication technology has become a phenomenon that can change the way people work and the presence of a geo-office, an office that can be geographically located anywhere, has to be considered. This is the essence of the development of information communication technology. Abstract in Bahasa Indonesia : Kemajuan perkembangan teknologi komunikasi informasi dengan kehadiran berbagai fitur-fitur teknologi memberikan berbagai kemudahan berkomunikasi dan pilihan-pilihan untuk bekerja di mana saja dan kapan saja. Perkembangan teknologi komunikasi informasi menjadi sebuah fenomena yang mengubah cara bekerja dan kehadiran geo-office, kantor yang secara geografis bisa berada di mana-mana perlu dipertimbangkan, ini adalah esensi kemajuan teknologi komunikasi informasi. Kata kunci: teknologi komunikasi, implementasi, geo-office.